THE IMPACT OF INTERNATIONAL SANCTIONS ON ACTIVITIES OF FOREIGN COMPANIES IN RUSSIA - A. S Linnikov (Финансы: теория и практика)
The author reveals the doctrinal and practical content of the “international economic sanctions” concept in relation to the activities of foreign companies in the Russian Federation. The paper examines the main types of economic sanctions against states, companies and individuals and analyzes the impact of restrictive measures on foreign companies and their personnel. The phenomenon of anti-Russian sanctions is viewed from the corporate point of view: the author analyzes a number of methodological guidelines introduced in large international companies specifically not to fall under the effect of sanctions. The author reveals the sanctions most dangerous for such companies in the context of internal corporate rules and policies and describes possible penalty measures for violation of the sanction regime. The author also addresses the issue of international and national law conflicts that international companies operating in the Russian Federation are inevitably faced with when working in the Republic of Crimea. In conclusion, the author proposes a number of recommendations for the Russian government authorities to overcome the negative impact of the so-called “sanctions” as well as to recognize and use the positive factors of the sanction regime to strengthen the economy of the Russian Federation